Statin intolerance – an attempt at a unified definition. Position paper from an International Lipid Expert Panel. (June 2015) - Banach, Maciej; Rizzo, Manfredi; Toth, Peter P; Farnier, Michel; Davidson, Michael H; Al-Rasadi, Khalid; Aronow, Wilbert S; Athyros, Vasilis; Djuric, Dragan M; Ezhov, Marat V; Greenfield, Robert S; Hovingh, G Kees; et al.
<x xml:space="preserve">Abstract</x> Statins are one of the most commonly prescribed drugs in clinical practice. They are usually well tolerated and effectively prevent cardiovascular events. Most adverse effects associated with statin therapy are muscle-related. The recent statement of the European Atherosclerosis Society (EAS) has focused on statin-associated muscle symptoms (SAMS), and avoided the use of the term 'statin intolerance'. Although muscle syndromes are the most common adverse effects observed after statin therapy, excluding other side effects might underestimate the number of patients with statin intolerance, which might be observed in 10 – 15% of patients. In clinical practice, statin intolerance limits effective treatment of patients at risk of, or with, cardiovascular disease. Knowledge of the most common adverse effects of statin therapy that might cause statin intolerance and the clear definition of this phenomenon is crucial to effectively treat patients with lipid disorders. Therefore, the aim of this position paper was to suggest a unified definition of statin intolerance, and to complement the recent EAS statement on SAMS, where the pathophysiology, diagnosis and the management were comprehensively presented.